STRATEGI DIVERSIFIKASI SEKTORAL UNTUK MEMINIMALISIR RISIKO PORTOFOLIO PADA MASA PEMULIHAN EKONOMI - Aries Veronica; Yeni Alfiana; Nadia Erlangga (Fakultas Ekonomi Universitas IBA, 2026)
The economic recovery period is characterized by heightened uncertainty and volatility in financial markets, which directly affects investment risk. Differences in recovery speed across economic sectors lead to uneven asset performance, making sector concentration a potential source of increased portfolio risk. This study aims to examine portfolio risk characteristics during economic recovery and analyze the role of sectoral diversification strategies in minimizing investment portfolio risk. The research employs a descriptive qualitative approach through a literature review, utilizing secondary data from academic journals, investment textbooks, and capital market reports. The findings indicate that sectoral diversification is effective in reducing unsystematic risk and portfolio volatility by combining sectors with different risk and return characteristics. Sectoral diversification also plays an important role in maintaining portfolio stability and return consistency, particularly during periods of ongoing economic recovery. The combination of defensive sectors with relatively stable performance and cyclical sectors with higher growth potential contributes to the formation of a more balanced and resilient portfolio. Therefore, sectoral diversification represents a relevant and effective strategy for portfolio risk management in the context of economic recovery.